2012
DOI: 10.1016/s1470-2045(12)70412-6
|View full text |Cite
|
Sign up to set email alerts
|

First-line erlotinib in patients with advanced non-small-cell lung cancer unsuitable for chemotherapy (TOPICAL): a double-blind, placebo-controlled, phase 3 trial

Abstract: SummaryBackgroundMany patients with advanced non-small-cell lung cancer (NSCLC) receive only active supportive care because of poor performance status or presence of several comorbidities. We investigated whether erlotinib improves clinical outcome in these patients.MethodsTOPICAL was a double-blind, randomised, placebo-controlled, phase 3 trial, done at 78 centres in the UK. Eligibility criteria were newly diagnosed, pathologically confirmed NSCLC; stage IIIb or IV; chemotherapy naive; no symptomatic brain me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
123
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(130 citation statements)
references
References 33 publications
6
123
0
Order By: Relevance
“…The multivariate analysis in this study showed that patients with stage IV disease had a higher risk for death than stage IIIb which is consistent with other studies, whereas the initial clinical stage affects the success of second-line chemotherapy 11,14 . From our study we observed that patients who had received platinum based as first-line treatment followed by taxanes containing regimen as second-line treatment had a better prognosis than others.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The multivariate analysis in this study showed that patients with stage IV disease had a higher risk for death than stage IIIb which is consistent with other studies, whereas the initial clinical stage affects the success of second-line chemotherapy 11,14 . From our study we observed that patients who had received platinum based as first-line treatment followed by taxanes containing regimen as second-line treatment had a better prognosis than others.…”
Section: Discussionsupporting
confidence: 91%
“…Some studies showed no difference in time to progression and OS between younger and elder patients (>70years) 12,13 . Others obtained a higher risk of death in patients aged 65 and older ones 14,15 . This discrepancy may be attributed to the small sample size of the current study.…”
Section: Discussionmentioning
confidence: 94%
“…In two trials evaluating an egfr tki compared with placebo in patients not suitable for chemotherapy, no clear differences in pfs or os were observed ( Table i). Statistical significance was reached in the trial by Lee et al 35 for pfs, but neither trial showed a difference in os 30,35 . Quality of life in the Goss et al 30 trial was not different between the two arms.…”
Section: Egfr Inhibitor Plus Chemotherapy Compared With Chemotherapy mentioning
confidence: 87%
“…Compelling clinical examples include epidermal growth factor receptor (EGFR) mutations and anaplastic lymphoma kinase (ALK) rearrangements (1,2). In both cases, patients with EGFR-mutant or ALK-rearranged advanced NSCLC are now routinely treated with kinase inhibitors (erlotinib or crizotinib, respectively) as opposed to chemotherapy as their initial systemic treatment for advanced cancer (3)(4)(5)(6). Several additional subsets of patients with NSCLC defined by an oncogenic driver genomic alteration, including mutations in BRAF and ERBB2 and rearrangements in ROS1 and RET, are similarly being treated in clinical trials to determine whether kinase inhibitors for these oncogenic proteins may represent an effective treatment approach (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%